Possible Involvement of MyD88 in Regulating Stress Response in Mice - Hosoi, Toru; Yamawaki, Yosuke; Kimura, Hitomi; Honda, Shoko; Ozawa, Koichiro (Frontiers in Neuroscience, 2021)
Myeloid differentiation primary response 88 (MyD88) is an adapter protein of the toll-like receptor (TLR) family that regulates innate immune function. Here, we identified a novel role of MyD88 in regulating stress response. MyD88 deficiency decreased immobility time in the forced swim test without affecting locomotor activity in mice. Immobilization stress-induced production of serum corticosterone was also completely inhibited by MyD88 deficiency. Stress induced decrease in glucocorticoid receptor in the hippocampus. On the other hand, stress exposure in MyD88 deficient mice did not cause decrease in its level in the hippocampus. Furthermore, immobilization stress-induced reduction of brain-derived neurotrophic factor (BDNF) levels in the hippocampus was ameliorated by MyD88 deficiency. These results suggest that MyD88 deficiency attenuates depression-like behavior by regulating corticosterone and BDNF levels. Overall, these results indicate the key role of MyD88 in regulating stress response in mice.